Clinical Implications of Digenic Inheritance and Epistasis in Primary Immunodeficiency Disorders - Ameratunga, Rohan; Woon, See-Tarn; Bryant, Vanessa L.; Steele, Richard; Slade, Charlotte; Leung, Euphemia Yee; Lehnert, Klaus (Frontiers in Immunology, 2018)
The existence of epistasis in humans was first predicted by Bateson in 1909. Epistasis describes the non-linear, synergistic interaction of two or more genetic loci, which can substantially modify disease severity or result in entirely new phenotypes. The concept has remained controversial in human genetics because of the lack of well characterized examples. In humans it is only possible to demonstrate epistasis if two or more genes are mutated. In most cases of epistasis the mutated gene products are likely to be constituents of the same physiological pathway leading to severe disruption of a cellular function such as antibody production. We have recently described a digenic family, who carry mutations of TNFRSF13B/TACI as well as TCF3 genes. Both genes lie in tandem along the immunoglobulin isotype switching and secretion pathway. We have shown they interact in an epistatic way causing severe immunodeficiency and autoimmunity in the digenic proband. With the advent of Next Generation Sequencing (NGS) it is likely other families with digenic inheritance will be identified. Since digenic inheritance does not always cause epistasis, we propose an epistasis index which may help quantify the effects of the two mutations. We also discuss the clinical implications of digenic inheritance and epistasis in humans with primary immunodeficiency disorders.